Implementasi Sistem Akuntansi Keuangan Berbasis Microsoft Access pada UMKM Marina Samudra Stationery - Itan, Iskandar; Meiviana, Meiviana (Journal Of Human And Education (JAHE), 2024)
In developing countries like Indonesia, SMEs play a crucial role in reducing unemployment and boosting GDP. However, many SMEs, including Marina Samudra Stationery in Batam, face significant challenges in efficient and structured financial record-keeping. To address this issue, a Community Service (PkM) activity was conducted by implementing a Microsoft Access-based accounting system. The methods employed included simulation of accounting information system implementation and training for the partner, with primary data collected through observation and interviews. The implementation process involved needs analysis, system design, development, testing, validation, and training and documentation. The results of this activity demonstrate that the Microsoft Access-based accounting system can significantly enhance the efficiency and accuracy of financial record-keeping, facilitate financial analysis and reporting, and support the management of larger data volumes. Despite challenges such as capacity limitations and technical maintenance needs, this activity is expected to help Marina Samudra Stationery overcome existing challenges and support the growth and sustainability of their business.